ARE PATIENTS SATISFIED WITH HOSPITAL FOOD? - Teng Seng-Chong; Esah Bahaman; Teng Wen-Yen (Malaysian Journal of Public Health Medicine, 2003)
Although only 6.3% of the 221 respondents in this cross-sectional study stated outright that the hospital food served to them was not good, a high proportion of respondents (62.0%) supplemented hospital food with outside food. When the reasons for supplementation were considered, it is likely that 53.8% ( ± 5.5%; 95% Cl) of the patients in this study were dissatisfied with hospital food for some reasons or other, particularly with regards to adequacy, variety, attractiveness and sen1ing time. The proportion of respondents who were dissatisfied with hospital food was significantly higher (p<0.05) among those with poor appetite during admission (17.9%) than among those with normal or good appetite (4.7%), signifying that patients' perception of hospital food is influenced by their appetite during admission. Breakfast, afternoon tea and the morning beverage were the meal and snacks with comparatively higher proportions of dissatisfied respondents, with the majority complaining of monotony and insufficient food and requesting for more Malaysian delicacies in the menu.